The Function of Commissioner Based on the Principles of Good Corporate Governance (Faculty of Law, Universitas Negeri Semarang, 2022)
The organs and functions of a limited liability company are controlled by Company Law No. 40 of 2007 Governing Limited Liability Companies (UU PT). The tasks of executing and supervising have been distinguished. The board of directors is in charge of the company's day-to-day operations, while the board of commissioners oversees the board of directors. In reality, however, the board of commissioners participates in the board of director activities or performs board of director tasks. This study aims to analyze the functions of commissioners and how they should be carried out in compliance with the laws and regulations governing corporate governance. Primary, secondary, and additional data are used in this study. The study found that the board of commissioners' role should be based on the Limited Liability Company Act. The board of commissioners serves as the board of directors' supervisor. Because shareholders also serve on the board of commissioners, the board of commissioners is involved in the operation of the board of directors. The Board of Commissioners' involvement in the Board of Directors' activities must be severely limited by the Board of Directors. If it turns out that the commissioners' activities are detrimental to the shareholders, the Board of Directors can bring this to a general meeting of shareholders and hold them accountable.